MENGUNGKAP DETERMINAN KINERJA PEGAWAI DARI MOTIVASI, INSENTIF DAN BEBAN KERJA - Yovita Mumpuni Hartarini; Tossy Aryanto; Frida Widyawati Triasningrum (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2026)
Performance is a term used to describe the level of achievement or results attained by an individual or organization in carrying out their tasks or work. In the context of an organization or company, performance is often measured by the extent to which set targets or objectives are achieved. This study is motivated by the low levels of motivation, incentives, and workload at the Pekalongan City Office of Tourism, Culture, Youth, and Sports at the beginning of 2024. The objectives of this study are to determine (1) the influence of motivation on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports, (2) the influence of incentives on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports, and (3) the influence of workload on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports. The population used in this study is all 35 civil servants at the Pekalongan City Office of Tourism, Culture, Youth, and Sports. The sample size in this study is 35 employees. The data collection technique used in this study is a questionnaire covering the variables of motivation, incentives, and workload. The analysis technique in this study is multiple linear regression analysis. The results of the study indicate that (1) work motivation has a significant effect on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports, as shown by a significance value of 0.028 < 0.05 and a t-value of 2.247 > t-table 1.68, (2) incentives have a significant effect on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports, as shown by a significance value of 0.021 < 0.05 and a t-value of 2.366 > t-table 1.68, and (3) workload does not have a significant effect on the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports, as shown by a significance value of 0.505 > 0.05 and a t-value of -0.671 < t-table 1.68. The study suggests that the organization should continue to enhance motivation, increase incentives, and pay attention to the workload assigned to employees. Future researchers are encouraged to add new variables that may influence the performance of employees at the Pekalongan City Office of Tourism, Culture, Youth, and Sports.